2014
DOI: 10.2147/bctt.s74663
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir phosphate monotherapy ablates tumor neovascularization, growth, and metastasis in mouse model of human triple-negative breast adenocarcinoma

Abstract: BackgroundTriple-negative breast cancers (TNBCs) lack the estrogen, progesterone, and epidermal growth factor (EGF) receptor-2 (HER2/neu) receptors. Patients with TNBC have typical high grading, more frequent relapses, and exhibit poorer outcomes or prognosis compared with the other subtypes of breast cancers. Currently, there are no targeted therapies that are effective for TNBC. Preclinical antitumor activity of oseltamivir phosphate (OP) therapy was investigated to identify its role in tumor neovascularizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The prostasphere volume from all the cell lines except PC3 decreased with increasing concentrations of OP. The decrease in spheroid volume could be due to either inhibition of matrix metalloprotease-9 (MMP-9)-mediated cell motility or cytotoxic effect 48,7678. It was reported that αvβ3 integrin cooperates with MMP-9 in breast cancer cell migration 79.…”
Section: Discussionmentioning
confidence: 99%
“…The prostasphere volume from all the cell lines except PC3 decreased with increasing concentrations of OP. The decrease in spheroid volume could be due to either inhibition of matrix metalloprotease-9 (MMP-9)-mediated cell motility or cytotoxic effect 48,7678. It was reported that αvβ3 integrin cooperates with MMP-9 in breast cancer cell migration 79.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these compounds are of interest for a variety of industrial applications in food ingredients, pharmaceuticals, and personal care products. The extension to incorporate OP in the formulation of MSPE was examined in the present study for its long-term stability and release to disable human cancer cells survival as previously described [ 7 , 8 , 11 , 13 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Surgically implanted PLGA-OP containing 20 mg OP and empty PLGA cylinders near the tumor site of heterotopic xenografts of human pancreatic PANC1 cancer cells in RAGxCγ double mutant mice impeded tumor neovascularization, growth rate, and metastatic spread to the liver and lungs compared with the untreated cohort [ 8 ]. Here, OP is used in the formulation because of its anticancer drug properties targeting mammalian neuraminidase 1 (Neu1) involved in multistage tumorigenesis [ 9 ] for pancreatic [ 10 ], triple negative breast [ 11 ] and ovarian [ 12 ] cancers. To this end, we engineered and developed OP-conjugated polymeric micelles prepared by RAFT living radical polymerization to target Neu1, which specifically bound Neu1 and activated receptor endocytosis and OP-micelle internalization [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies show that level of EDP in serum of patients is higher in patients with large tumor size (43). Blocking Neu-1 with oseltamivir phosphate (Tamiflu R ) or a Neu-1 siRNA in mammary carcinoma cells, MCF-7, and MDA-MB-231 cell lines, inhibits cell growth (44). Additional studies also point out an inhibition of tumor neovascularization growth and metastasis under oseltamivir phosphate treatment in mouse model of breast cancer that mimics human triple-negative breast cancer (45).…”
Section: Neu-1 Tm Domain As a Potential Target In Cancersmentioning
confidence: 99%